The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fmolb.2021.745990
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Promotes Hepatocellular Carcinoma Progression Synergistically With Hepatic Stellate Cells via Facilitating the Expression and Secretion of ENPP2

Abstract: Background: Hepatitis B virus (HBV) infection is a major risk factor causing hepatocellular carcinoma (HCC) development, but the molecular mechanisms are not fully elucidated. It has been reported that virus infection induces ectonucleotide pyrophosphatase-phosphodiesterase 2 (ENPP2) expression, the latter participates in tumor progression. Therefore, the aim of the present study was to investigate whether HBV induced HCC malignancy via ENPP2.Methods: HCC patient clinical data were collected and prognosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Bioinformatics analysis of TCGA high-throughput RNA sequencing data revealed that the expression of ENPP2 was significantly increased in liver cancer compared to adjacent normal liver tissue, which is consistent with previous studies. [14,18] Furthermore, by integrating clinical data from TCGA, we discovered a significant correlation between abnormal expression of ENPP2 and gender and clinical grouping in liver cancer. To further investigate the prognostic significance of ENPP2 in HCC, we analyzed several outcomes using the Kaplan-Meier Plotter database.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Bioinformatics analysis of TCGA high-throughput RNA sequencing data revealed that the expression of ENPP2 was significantly increased in liver cancer compared to adjacent normal liver tissue, which is consistent with previous studies. [14,18] Furthermore, by integrating clinical data from TCGA, we discovered a significant correlation between abnormal expression of ENPP2 and gender and clinical grouping in liver cancer. To further investigate the prognostic significance of ENPP2 in HCC, we analyzed several outcomes using the Kaplan-Meier Plotter database.…”
Section: Discussionmentioning
confidence: 91%
“…Bioinformatics analysis of TCGA high-throughput RNA sequencing data revealed that the expression of ENPP2 was significantly increased in liver cancer compared to adjacent normal liver tissue, which is consistent with previous studies. [14,18]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver cancer (LC) is known as the fourth major cause of cancer‐related death, and hepatocellular carcinoma (HCC) is the most common pathological subtype, taking up 75–85% of all primary cases of LC 1 . HCC patients often have an unfavorable prognosis due to the high metastasis and recurrence rate 2 . Besides, early symptoms of HCC are insidious, and a large number of patients are already in the advanced stage when they are diagnosed, missing the optimal treatment period 3 .…”
Section: Introductionmentioning
confidence: 99%
“…metastasis and recurrence rate. 2 Besides, early symptoms of HCC are insidious, and a large number of patients are already in the advanced stage when they are diagnosed, missing the optimal treatment period. 3 In recent decades, multiple RNAs, genes, and signaling pathways have been reported to partake in the tumorigenesis and progression of HCC.…”
mentioning
confidence: 99%